Pengukuran dan Analisis High Frequency Current Transformer Pendeteksi Partial Discharge - Andi Junaidi (KILAT, 2021)
The lifetime of high voltage equipment is very dependent on the condition of insulation, poor insulation means the life span of high voltage equipment is getting shorter. Partial Discharge is one of the causes of deterioration of high voltage equipment insulation. The ability to know the phenomenon of partial discharge in equipment becomes very important and adds value to the maintenance of high voltage equipment. Many explanations regarding partial discharge, partial discharge is the lack of uniformity of the electric field in the isolation or dielectric media which will result in the phenomenon of Partial Discharge where this will lead to the failure of the isolation media. Partial Discharge that occurs continuously can cause damage (breakdown) on a high voltage equipment. Therefore, before a high voltage device is used, Partial Discharge detection is necessary. Partial Discharge Detection can use the Partial Discharge measurement circuit. In testing partial discharges can be tested using a sensor with various circuits including High Frequency Current Transformers (HFCT) so that this research will discuss one part of the Partial Discharge measurement circuit, the HFCT detector. Hopefully, the HFCT detector can be further developed and can be used for better partial discharge detection.